Penyelenggaraan Pendidikan Guru Di Era Revolusi Kemerdekaan Indonesia 1945-1949 - Mohammad Rikaz Prabowo (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2024)
At the beginning of independence, in 1945-1949, Indonesia experienced a shortage of teachers which resulted in low educational standards. Plus the security conditions where the Dutch tried to thwart Indonesian independence. This research aims to determine teacher development during the 1945-1949 revolution, existing teacher education schools, and obstacles to teacher education. The historical method used through the stages of heuristics, verification, interpretation and historiography obtained the following results. First, changes to the education sector to replace the colonial system were formulated through several formulations, one of which was to meet the teacher shortage. The Education Congress of 1947 determined that education was oriented towards cultivating a spirit of patriotism and willingness to sacrifice. Second, to immediately overcome the teacher shortage, the government established Teacher School C (2 years), Teacher School B (4 years), and Teacher School A (3 years). Vocational teacher schools were also established, such as the Technical Teachers School (KGST), the Women's Skills Teachers School (SGKP), and the Islamic Religious Teachers and Judges School (SGHAI). Third, obstacles to teacher education in this era are not only caused by domestic security conditions, but also due to limited teacher educators and a lack of facilities and teaching materials. For secondary and vocational school teaching, only MO A and B Diploma courses are available. In addition, many teachers' school students choose to join the national defense effort.